Chemotherapy Versus Chemoradiation as Preoperative Therapy for Resectable Pancreatic Ductal Adenocarcinoma: A Propensity Score Adjusted Analysis. Issue 2 (February 2019) - Cloyd, Jordan M.; Chen, Hsiang-Chun; Wang, Xuemei; Tzeng, Ching-Wei D.; Kim, Michael P.; Aloia, Thomas A.; Vauthey, Jean-Nicolas; Lee, Jeffrey E.; Katz, Matthew H.G.
Abstract : Objectives: Although the use of neoadjuvant therapy for resectable pancreatic ductal adenocarcinoma is increasing, the optimal preoperative treatment regimen remains poorly defined. Methods: All patients with resectable pancreatic ductal adenocarcinoma who received preoperative chemotherapy alone (12%) or chemoradiation therapy (CRT) alone (88%) before pancreatectomy between 1999 and 2014 were included. Propensity score matching with inverse probability weighting was conducted based on age, baseline carbohydrate antigen 19-9, and procedure type. Results: Patients who received preoperative CRT were more likely to undergo a margin negative (91% vs 79%, P < 0.01) and node negative (53% vs 23%, P < 0.01) resection and experience less locoregional recurrence (LR; 16% vs 33%, P < 0.01) but similar median overall survival (OS; 33.6 vs 26.4 months, P = 0.09). On multivariate analysis, carbohydrate antigen 19-9 (hazard ratio, 1.2; 95% confidence interval [CI], 1.1–1.3) and positive lymph nodes (hazard ratio, 1.5; 95% CI, 1.0–2.2) were associated with OS, whereas tumor size (odds ratio [OR], 1.5; 95% CI, 1.3–1.8), positive lymph nodes (OR, 3.1; 95% CI, 1.8–5.6), and preoperative chemotherapy (OR, 1.8; 95% CI, 1.1–2.9) were associated with LR. Conclusions: Preoperative CRT is associated with less margin and lymph node positivity, reduced LR, and similar OS compared with preoperative chemotherapy.